Economic Evaluation And Willingness To Pay (Wtp) Elicitation Of Dengue Vaccine In Malaysia - Yeo, Hui Yee (2017)
Dengue disease poses great health and economic burden in Malaysia. This study was divided into two phases. Phase-1 evaluated the impact and cost-effectiveness of dengue vaccine employing a dynamic-transmission mathematical model from both public provider and societal perspective. The model integrated Malaysia-specific epidemiological data, pooled efficacy and long-term safety data from phase-III clinical studies, and sensitivity analyses to refine the estimates from previous studies. Phase-2 assessed the acceptance and willingness-to-pay (WTP) value of dengue vaccine among Penang general population utilizing a cross-sectional, contingent-valuation approach. A double-bounded dichotomous-choice approach was applied in eliciting the WTP amount via bidding game method. The mean WTP value and the factors affecting the WTP value were determined by a parametric two-part model (TPM). The association between dengue vaccine acceptance and its determinants was analysed by a univariate logistic regression model.